Kebijakan Moratorium PNS : Analisis Bezetting Pegawai, Rightsizing Kelembagaan, dan Budgeting Penyelenggaraan Pemerintahan - Ajib Rakhmawanto (Pusjar SKPP Lembaga Administrasi Negara, 2016)
Professional civil servant management based on merit system is needed to support government’s tasks. The arrangement on number, qualification, composition, and distribution of civil servants is required to rationalize civil servants’ placement in order to improve their competencies and working performances. Moratorium policy is a temporary delay of civil servant recruitment to find out the actual employee needs based on the quantity and quality aspects. The goal of this study is to analyze the strategic issues to be used as recommendations in creating civil servant moratorium policy on some aspects, such as bezetting, organization rightsizing, business process, and the government budgeting. This study is a policy research using a qualitative descriptive approach, conducted with a Focus Group Discussion (FGD) method that produces primary data and documentation study that leads to secondary data. This study shows that civil servant moratorium policy is still relevant to be extended since it is viewed in the bezetting aspect: high number of employees is hired yet they are in poor quality. Then the organizational rightsizing is not conducted in a comprehensive structure particularly at regional government in which the business process is still far from ideal.The government budgeting is not ideal between employees’ salary expenditure and development expenditure in which the composition of employees’ salary expenditure is higher than the development expenditure.Keywords: moratorium, bezetting, rightsizing, budgetingPengelolaan PNS yang profesional berbasis merit diperlukan untuk menunjang kelancaran pelaksanaan tugas-tugas pemerintahan. Rasionalisasi penempatan PNS yang mengarah pada peningkatan kompetensi dan prestasi kerja memerlukan adanya penataan pada jumlah, kualifikasi, komposisi, dan distribusi. Kebijakan moratorium merupakan penundaan sementara penerimaan PNS untuk menciptakan kebutuhan riil dari sisi kuantitas maupun kualitas. Kajian ini menganalisis isu-isu strategis sebagai bahan rekomendasi untuk mengambil kebijakan moratorium PNS pada aspek bezetting pegawai, rightsizing kelembagaan dan tatalaksana, serta budgeting pemerintah. Kajian ini merupakan policy research dengan pendekatan deskriptif kualitatif menggunakan metode Focus Group Discussion(FGD) yang menghasilkan data primer dan studi dokumentasi yang menghasilkan data sekunder. Hasil kajian menunjukan bahwa moraturium PNS masih relevan dilanjutkan karena dilihat dari aspek bezetting pegawai secara kuantitas banyak tetapi secara kualitas sedikit, rightsizing kelembagaan belum menyeluruh khususnya pada pemerintah daerah dengan tatalaksana yang masih kurang sempurna, budgeting pemerintah belum ideal antara belanja pegawai dengan belanja pembangunan yang komposisinya lebih besar pada belanja pegawai.Kata kunci: moratorium, bezetting, rightsizing, budgeting